Paternal identification of mango controlled-pollination seedling progenies based on fluorescent SSR markers - YAN Jinyuan; ZHENG Bin; WANG Songbiao; MA Xiaowei; XU Wentian; XIE Kunliang; WU Hongxia (Guoshu xuebao, 2025)
[Objective] Mango (Mangifera indica L.), an evergreen species of the genus Mangifera in the family Anacardiaceae, is widely cultivated in tropical and subtropical regions worldwide. The dominant mango varieties in China are limited and mainly imported from abroad, resulting in an unbalanced plantation structure and a highly concentrated fruit ripening period. Hybrid breeding is very important in the selection of new mango cultivars, which can be divided into artificial pollination hybridization and natural pollination hybridization. It is possible to speed up the breeding process by performing genotyping on naturally pollinated seedlings of known female parent varieties at the seedling stage to identify the optimal male parents. Traditional morphological identification is limited due to influence by environmental factors and plant growth conditions. Marker assisted selection, based on DNA polymorphisms among progeny individuals, is a new generation technology for rapid and accurate identification of genotype of seedlings. Simple Sequence Repeat (SSR) markers are abundant, co-dominant, highly polymorphic, easy to utilize, and not influenced by environmental factors or plant morphological characteristics. Fluorescent SSR markers with distinct fluorescent labels (FAM, HEX and ROX) at the 5' end combined with capillary electrophoresis-based genotyping platforms, offer advantages such as high efficiency, high accuracy and high automation. This study aimed to use fluorescent SSR markers for paternal identification in controlled-pollination lines of mango, in order to provide valuable insights for germplasm innovation and selection of new cultivars. [Methods] A total of 113 controlled-pollinated seedling progeny and 12 parental varieties were collected as research materials from the germplasm repository of the South Subtropical Crops Research Institute of the Chinese Academy of Tropical Agricultural Sciences.10 pairs of fluorescent SSR markers, previously developed by our research group from the mango genome, were used in combination with capillary electrophoresis, to identify the paternal parent of individual seedling progeny at the seedling stage. The genomic DNA of the samples was extracted using an improved CTAB method. The quality and concentration of the DNA was assessed using a 1% agarose gel and a Nano Drop One (Thermo Scientific). The DNA concentration was uniformly adjusted to 30 ng·µL-1 and frozen at -20 ℃ for future use. The PCR amplification reaction system, with a total volume of 20 µL, consisted of 2 µL of DNA template, 0.5 µL of upstream primer (10 µmol·L-1), 0.5 µL of downstream primer (10 µmol·L-1), 10 µL of 2×EasyTaq PCR SuperMix, and 7 µL of ultrapure water. The PCR programme consisted of the following steps: pre-denaturation at 94 ℃ for 5 minutes; 35 cycles of 94 ℃ for 30 seconds, 58 ℃ for 30 seconds, and 72 ℃ for 30 seconds; extension at 72 ℃ for 8 minutes; and storage at 4 ℃ for later use. The paternal analysis used the maximum likelihood method, and the implementation of the maximum likelihood method was based on Cervus V3.07 software. [Results] A total of 54 alleles were detected in 125 mango resources using 10 pairs of SSR primers, with an average of 5.4 alleles per SSR primer. The Shannon information index (I) ranged from 0.926 to 1.428, with an average of 1.185. The mean observed heterozygosity (Ho) and expected heterozygosity (He) were 0.689 and 0.632, respectively. The polymorphism information content (PIC) ranged from 0.452 to 0.677, with an average of 0.575. Out of 113 offsprings, 95 were successfully identified for the optimal paternal parent, with a success rate of 84.07% and a confidence level of over 80%. Of them, 80 were hybrid offsprings, accounting for 84.21%, while 15 were self-pollinated offsprings, accounting for 15.79%. At a 95% confidence level, 47 offsprings successfully identified for the optimal paternal parent, giving a success rate of 41.59%. Of them, 44 were hybrid offsprings, accounting for 93.62%, and e 3 were self-pollinated offsprings, accounting for 6.38%. A UPGMA cluster analysis was performed on 95 offsprings and 10 parental varieties. The results showed that most of the offsprings clustered with either their paternal or maternal parent, showing a clear genetic tendency. The offsprings with Zill as the maternal parent were mostly clustered close to the maternal parent, showing a maternal genetic tendency, for example, H3, H34, and H35 were clustered with the maternal parent Zill. Similarly, almost all the offsprings with Dashehari as a maternal parent were clustered with the maternal parent, showing a clear maternal genetic tendency. However, H10, H18, and H22 were not clustered closely with either the maternal or paternal parent. [Conclusion] A total of 95 offsprings were matched to the optimal paternal parent, with a success rate of 84.07% and a confidence level of over 80%. The genetic tendency of the progeny towards either maternal or paternal inheritance. This result would provide a reference for mango germplasm innovation and variety breeding. The fluorescent SSR molecular marker technology could quickly and accurately identify the paternal parent of mango hybrid offspring, and would be used as a tool for early screening of hybrid seedlings.